BRAND IMAGE, USABILITY APLIKASI DAN PROMOSI TERHADAP REORDER CUSTOMER GRAB DI KOTA SOLO - Wahid Ali Imron; Sudarwati Sudarwati; Istiqomah Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2020)
Reorder is the most important thing in corporate marketing, Reorder itself can be influenced by several things. This study aims to determine the simultaneous and partial influence of the variables Brand Image, Application Usability, and Promotion on Reorder on Grab Customer in Solo. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing Reorder on Grab Customer in Solo City. The method used is descriptive quantitative method. The population is all Grab customers in the city of Solo. The sample used was 100 people with purposive sampling method. The research data analysis method is multiple linear analysis. The result is that the independent variables simultaneously influence the dependent variable having a siginfikansi 0.000